Áp dụng trò chơi vận động trong giờ học giáo dục thể chất của sinh viên trường đại học văn hóa Hà Nội - Nguyễn, Ngọc Quý (Tạp chí giáo dục và xã hội, 2023)
Renovating the content of subjects in general and physical education subjects at Hanoi University of Culture in particular is becoming urgent. The inclusion of movement game content in the physical education class helps the subject not to become hard and tiring, thereby having a good impact on physical education education for students to help them complete the subject well. his study.